Photo-Diodes Based on CH3NH3PbCl3 Perovskite Single Crystals by Epitaxial Growth for Ultraviolet Photo-Detection - Zhao, Jingda; Wang, Xin; Pan, Yuzhu; Xu, Yubing; Li, Yuwei; Chen, Jing; Wu, Jun; Li, Qing; Zhao, Zhiwei; Zhang, Xiaobing; Akram, Javed; Bae, Byung Seong; et al. (Frontiers in Physics, 2021)
Organic-inorganic hybrid methylammonium lead halide perovskite MAPbX3 (where MA = CH3NH3, and X= Cl, Br, I) single crystals are potential semiconductors for photo-detection due to their excellent optoelectronic performance. Specially, MAPbCl3 single crystal is wide-band-gap (2.9 eV) semiconductor which is suitable for ultraviolet (UV) detection. In this work, n -n+ photo-diodes are fabricated through solution-processed epitaxial growth, growing Bi-doped MAPbCl3 epitaxial layer on MAPbCl3 single crystal substrate. The epitaxial layer effectively improves the interface between n–type and n+-type layers and leads to low dark current. This work provides useful information for UV detection based on perovskites.